Effect of smartphone addiction on reaction time in geriatric population - Simran Grewal; Rajneet Kaur Sahni (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2019)
Context: Mobile phones have entered our lives through technological developments, becoming the most commonly used technological device, there advances have had a huge impact on many walks of life. Technology gives human beings good effects such as convenient everyday life. There has been a progressive increase in both the number and proportion of the aged in India over time and as age advances there is decline in motor and cognitive functioning. As the age increases, the reaction time also seems to increase. Older adults can benefit from the use of smartphones in a number of ways.  Aims: The aim of this study was to observe the Effect of Smartphone Addiction on Reaction time (RT) in Elderly Population. Setting and design: This was an experimental study.  Subjects and methods: Ninety elderly subjects were enrolled for the study by random sampling in and around from Ludhiana. They all used a Smartphone for several hours per day. The subjects were divided into 3 groups A, B and C of 30 each both male and female according to the scores on Mobile Phone Addiction Scale (MPAS). Simple reaction time was estimated by Ruler Drop Method (RDM). The RT (in seconds) of each participant was calculated with the standard conversion equation. Statistical analysis used: The data was analysed using mean, standard deviation (SD), and Pearson's correlation. Results: The comparison of Ruler Drop Method between group A, B and C. The Mean+SD value of Group A is 0.27+0.040, the Mean+SD value of Group B is comparatively low 0.23+0.027 and the Mean+SD value of group C is low than group A and B 0.20+0.032. The value of Pearson correlation between MPAS and Ruler drop method is -0.656 which is statistically significant.  Conclusion: The study concludes that the group with high MPAS score has low RT compared to low and moderate groups.